Foamed concrete based on wood wax oil modification and preparation method thereof

Through the synergy between modified wood wax oil and other components, the structural stability, water resistance and green and low-carbon problems of foamed concrete are solved, the uniformity and long-term durability of foam are achieved, and the comprehensive performance of concrete is improved.

CN120247502AActive Publication Date: 2025-07-04SHANGHAI TUNNEL PORT BUILDING MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510761421.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-07-04
Estimated Expiration
2045-06-09

AI Technical Summary

Technical Problem

Traditional foamed concrete has poor structural stability, uneven pore structure, insufficient water resistance, prominent compatibility problems, and green and low-carbon demand has not been met.

Method used

By grafting and esterifying the wood wax oil with nonylphenol polyoxyethylene ether, modified wood wax oil is prepared, combined with components such as polyacrylamide, n-pentanol, polyoxyethylene polyoxypropylene ether and silica aerogel particles, a hydrophobic protective film and crosslinking network are formed, foam stability and hydration reaction are optimized, and a multi-stage pore structure is constructed.

Benefits of technology

It improves the water resistance, frost resistance, mechanical properties and environmental adaptability of foamed concrete, enhances the stability and durability of foam, and improves lightweight and thermal insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses foamed concrete based on wood wax oil modification and a preparation method thereof, and relates to the technical field of concrete materials. According to the foamed concrete, the modified wood wax oil is introduced into a traditional foamed concrete system, so that the water resistance, the freezing resistance and the mechanical property of the foamed concrete are enhanced, and meanwhile, the foam stability and the pore structure uniformity are improved. The modified wood wax oil is prepared by carrying out graft esterification reaction on wood wax oil and nonylphenol polyoxyethylene ether, the esterification rate of a graft product is not lower than 65%, and the HLB value is controlled between 8 and 11. Through modification of the grafted product, the wood wax oil can be compatible with a cement matrix, a cement hydration reaction is promoted, and a compact protective layer is formed on the surface of a foam film, so that the impermeability, freezing resistance and mechanical strength of foamed concrete are effectively improved. The foamed concrete has a wide application prospect in buildings, heat preservation, sound insulation and energy-saving projects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and particularly to a foamed concrete modified with wood wax oil and a preparation method thereof. Background Art

[0002] Foamed concrete is a porous lightweight building material made by mixing components such as cement-based binders, foaming agents, water, and lightweight aggregates, and is widely used in insulation layers, sound insulation layers, and lightweight filling fields. Its porous structure endows it with good thermal insulation performance and low bulk density, making it suitable for weight reduction and energy-saving projects in high-rise buildings.

[0003] With the expansion of application scenarios, higher requirements are put forward for the comprehensive performance of foamed concrete materials, especially in terms of impermeability, frost resistance, durability, and environmental adaptability. However, the traditional foamed concrete system generally has the following problems: First, the structural stability is poor. During construction or use, the bubbles in the foaming system are prone to rupture or collapse, resulting in uneven pore structure and affecting the mechanical properties and insulation effect of the final material. Second, the water resistance is insufficient. The porous structure is easy to absorb moisture, has a high water absorption rate in a humid environment, and is prone to cause a decline in thermal performance and freeze-thaw damage, restricting its long-term application in high-humidity and high-cold regions. Third, the compatibility problem is prominent. Some admixtures introduced to improve performance may have problems such as poor dispersion, weak interfacial bonding, and unstable system due to large differences in physical and chemical properties from the cement-based system. Fourth, the green and low-carbon requirements have not been met. At present, some materials for improving performance come from chemical synthesis systems, and there are certain limitations in terms of environmental protection and sustainability, making it difficult to fully meet the current development trend of green building materials.

[0004] To overcome the above deficiencies, various explorations have been carried out at home and abroad in the raw material system, proportion design, foaming agent type, and interfacial enhancement means of foamed concrete. For example, some studies have tried to introduce natural organic substances, inorganic micro-nano fillers, or polymer functional materials to improve the foam stability or pore wall structure performance, but generally there are still problems such as low modification efficiency, poor system stability, and weak process adaptability.

[0005] Therefore, how to further improve the impermeability, durability, and environmental adaptability of foamed concrete without affecting the stability of the foaming system and the cement hydration reaction is still a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a foamed concrete modified with wood wax oil and a preparation method thereof.

[0007] The above object of the present invention is achieved by the following technical solutions: A foamed concrete modified with wood wax oil, which is prepared from the following components in parts by weight: Cement: 30 - 40 parts; Modified wood wax oil: 7 - 9 parts; Protein foaming agent: 0.2 - 0.4 parts; Deionized water: 25 - 35 parts; Lightweight sand: 18 - 20 parts; The modified wood wax oil is a graft product after the grafting esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65%, and the HLB value is 8 - 11.

[0008] Wood wax oil itself, as a natural hydrophobic substance, can form a hydrophobic protective film in concrete to prevent water penetration and reduce the contact between the cement matrix and external water, which plays an important role in improving the water resistance and frost resistance of concrete. However, the hydrophobic characteristics of wood wax oil also make it difficult to be uniformly combined with the hydrophilic cement matrix, which may hinder cement hydration and reduce the strength and durability of concrete. In the present invention, wood wax oil is reacted with nonylphenol polyoxyethylene ether through graft modification, successfully changing the interfacial behavior of wood wax oil, making it have moderate hydrophilicity and good interfacial activity, so that it can be better compatible with the cement matrix. Specifically, the esterification rate of the prepared graft product is controlled to be not less than 65%, ensuring that a sufficient number of hydrophilic polyoxyethylene chain segments are effectively grafted onto the wood wax oil molecules. This degree of esterification guarantees the stability of its interfacial structure and functional performance; at the same time, its HLB value is controlled between 8 - 11, which not only avoids the decrease in the ability to form a hydrophobic film due to excessive hydrophilicity, but also ensures its good dispersibility and emulsifying performance in the cement-based slurry.

[0009] The modified wood wax oil not only retains its original hydrophobic groups, can self-assemble on the surface of cement particles to form a microcapsule-like coating structure, establishing a hydrophobic barrier to effectively prevent water diffusion, but also can adsorb and orientate with cement particles through its hydrophilic end to form a stable interfacial bond. This structure, without inhibiting cement hydration, synergistically promotes the formation and distribution of hydration products such as C-S-H gel, effectively improving the early strength and long-term durability of the slurry. In addition, under the synergistic action with the foaming agent, the modified wood wax oil migrates and orientates on the surface of the foam film to form a dense composite film structure, improving the elasticity of the foam film and the interfacial toughness, significantly enhancing the stability and anti-rupture performance of the foam, thereby improving the tolerance of the foam during stirring, pouring and initial setting processes, and finally enabling the foamed concrete to have a more uniform pore structure and higher structural integrity after forming.

[0010] Furthermore, the modified wood wax oil is prepared through the following steps: (1) Mix wood wax oil and nonylphenol polyoxyethylene ether in a mass ratio of 1:1.1 - 1.3, and add titanium tetrafluoride catalyst with a dosage of 0.5 - 1.5 wt% of the total mass of the reaction system for heating reaction; control the reaction temperature at 80 - 90 °C and the reaction time at 2 - 4 hours; Among them, the average EO unit number of nonylphenol polyoxyethylene ether is 9 - 11; the content ratio of C16 - C18 saturated fatty acid esters in the used wood wax oil is 65 - 85%; (2) Remove unreacted components by solvent to obtain a modified wood wax oil grafting product.

[0011] In the present invention, by modifying wood wax oil, a grafting product with both hydrophobic and hydrophilic structures is prepared, so as to achieve its efficient dispersion and functional synergy in the foamed concrete system. The traditional wood wax oil molecular structure is mainly composed of long-chain fatty acid esters, which has significant hydrophobicity, is difficult to be evenly distributed in the cement-water system, and is easy to aggregate into clusters, resulting in phase separation at the microscale, which not only affects the stability of the foam structure but also interferes with the normal hydration process of cement. To solve the above problems, nonylphenol polyoxyethylene ether with a polyoxyethylene chain segment is selected as the hydrophilic modifier in the present invention, and grafting esterification reaction is carried out with wood wax oil under specific conditions, thereby endowing the wood wax oil molecules with appropriate hydrophilicity and surface activity. The reaction is carried out under the catalysis of titanium tetrafluoride in a temperature-controlled environment of 80 - 90 °C for 2 - 4 hours, and the mass ratio of the reactants is controlled at 1:1.1 - 1.3, so that the reaction system has good reaction kinetics matching and can form an interfacial active product with a high grafting efficiency.

[0012] By regulating the reaction conditions and raw material characteristics, such as selecting nonylphenol polyoxyethylene ether with an EO number of 9 - 11, it helps to form a hydrophilic chain segment with an appropriate length in the grafting product, and control its HLB value in the range of 8 - 11; at the same time, the content ratio of C16 - C18 saturated fatty acid esters in the basic wood wax oil reaches 65 - 85%, ensuring a stable source of the hydrophobic group of the product, and enabling the modified wood wax oil to obtain good interfacial tunability while retaining the hydrophobic function. After the grafted product is removed of unreacted impurities by solvent extraction, an interfacial active agent-type material with uniform structure and excellent dispersibility is obtained.

[0013] The modified wood wax oil can not only quickly form a stable dispersion state in the cement system, but also participate in the adsorption and self-assembly process on the surface of cement particles at the micro level to form a multi-level cooperative interface. Its hydrophobic group provides a hydrophobic barrier in the early stage of hydration, inhibits the infiltration of capillary water, and improves the early waterproof ability; while the hydrophilic chain segment reduces the risk of aggregation between cement particles by regulating the charge distribution and spatial structure, promotes the regular generation of hydration products, and enhances the microstructural integrity of the paste.

[0014] Furthermore, 1 to 2 parts by weight of polyacrylamide are added to the foamed concrete.

[0015] The present invention significantly improves the stability of foam in foamed concrete by adding polyacrylamide. After polyacrylamide is added to foamed concrete, it synergizes with wood wax oil to improve the stability of the foam film and the elasticity of the foam structure. Specifically, the molecular structure of polyacrylamide has a hydrophilic group, which can interact with the hydrophilic segment in the modified wood wax oil to form a composite structure, which can form a strong cross-linked network on the surface of the foam liquid film, ensuring that the foam is not easy to collapse or break, and improving the overall foam stability of the foamed concrete. Therefore, during the molding process of the foamed concrete, the uniformity of the pore structure can be effectively maintained, thereby improving the lightness, thermal insulation and mechanical properties of the concrete.

[0016] Furthermore, 0.1 to 0.5 parts by weight of n-pentanol is added to the foamed concrete.

[0017] n-Pentanol has a moderate volatilization rate and good interfacial activity. When n-pentanol is dispersed in the foam liquid film, it can evaporate rapidly during the foam generation and molding process, thereby inducing a significant interfacial tension gradient in the local part of the foam film. This interfacial tension gradient acts as a driving force, prompting the structural units with both hydrophobic and hydrophilic properties in the modified wood wax oil molecules to undergo directional migration and enrichment, and preferentially arrange at the foam film interface.

[0018] Through this migration and interface reconstruction mechanism, the modified wood wax oil can quickly form a dense and orderly arranged hydrophobic protective layer on the foam surface, effectively reducing the sensitivity of the foam film to external disturbances (such as shear, vibration, and local liquid flow), and improving the tensile strength and rupture delay performance of the foam film. At the same time, the volatilization of n-pentanol takes away part of the water in the liquid film, causing the foam film thickness to be moderately thinned and forming a uniform and dense foam film structure, further slowing down the foam collapse trend caused by gravity drainage and thinning between films.

[0019] With the directional migration of modified wood wax oil and the cross-linked network formed with the assistance of polyacrylamide, the overall interfacial tension distribution of the foam liquid film is more stable, the elasticity of the membrane surface is enhanced, and the foam life in the system can be increased to more than twice that of the original system, significantly improving the foam retention and pore uniformity of the foamed concrete during mixing, pouring and initial setting. The resulting foamed concrete not only has higher pore structure integrity and lightweight performance, but also exhibits better waterproofness, frost resistance and mechanical stability during long-term service.

[0020] Furthermore, 1 to 3 parts by weight of polyoxyethylene polyoxypropylene ether is added to the foamed concrete, and the modified wood wax oil and polyoxyethylene polyoxypropylene ether are premixed at 25 to 35° C. to form an emulsified premix, and then mixed with other components to prepare the foamed concrete.

[0021] By introducing poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) block copolymer (Pluronic F127 is used in the present invention), a temperature-responsive emulsified microstructure is constructed in the system. Poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) exhibits lower critical solution temperature (LCST) behavior near 25-35 °C. In this temperature range, it can induce the formation of micelle structures, where the hydrophobic polypropylene oxide segment (PPO) serves as the core and the hydrophilic polyethylene oxide segment (PEO) serves as the shell, effectively encapsulating the modified wood wax oil in the micelle core.

[0022] This micelle encapsulation not only improves the dispersibility and stability of the modified wood wax oil in the aqueous phase but also realizes the controlled release of wood wax oil during the temperature change of the system. As the cement paste hydrates and releases heat and the ambient temperature rises, the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) micelles undergo structural relaxation and decomposition, releasing the encapsulated small droplets of modified wood wax oil. After release, these microscale wood wax oil droplets can spontaneously enrich on the surface of surrounding cement particles, forming a local hydrophobic microenvironment.

[0023] In this local microenvironment, due to the repulsion effect of the hydrophobic droplets on the surrounding moisture, it promotes the local concentration of moisture around the droplets, significantly increasing the concentration of local hydroxide ions (OH - ). This concentration effect accelerates the hydration reaction on the surface of cement particles, especially promoting the ordered and oriented growth of hydration products such as C-S-H gel. Compared with traditional uniform hydration, the oriented hydration structure formed under the induction of wood wax oil has higher compactness and coherence, significantly improving the early strength and long-term mechanical properties of foamed concrete.

[0024] In addition, after the oriented release, the modified wood wax oil can still form a hydrophobic barrier on the pore surface, further enhancing the waterproofness and durability of foamed concrete. Therefore, through the emulsification premixing and temperature-controlled release mechanism, the present invention realizes the dual regulation of the functionality of wood wax oil: on the one hand, it stabilizes the foam film during the foam generation stage, and on the other hand, it promotes the optimization of the microstructure during the hydration process of the paste, thus significantly improving the comprehensive performance of foamed concrete.

[0025] Furthermore, 0.5-1.5 parts by weight of silica aerogel particles are added to the foamed concrete, and the D50 particle size of the silica aerogel particles is 30-50 nm.

[0026] By introducing nano-scale silica aerogel particles, an auxiliary capillary network with a high specific surface area and a multi-level pore size distribution is constructed inside the foamed concrete. The aerogel particles themselves have a highly porous three-dimensional structure with a pore size range mainly concentrated between 20 and 200 nm. When uniformly dispersed in the cement-based system, they can introduce a large number of stable nano-capillary channels into the microstructure of the paste.

[0027] This multi-level capillary network is rapidly formed in the early stage of hydration, and can regulate the pore structure and liquid migration path at the microscale. When the modified wood wax oil is released and dispersed in the paste in the form of micro-droplets, relying on its low surface tension characteristics, the wood wax oil can rapidly penetrate and fill these nano-capillary channels under the drive of the local negative pressure gradient and capillary attraction. This penetration process not only realizes the deep distribution and uniform filling of the modified wood wax oil inside the system, but also effectively repels the free water in the pores during the penetration process, forming a hydrophobic liquid film.

[0028] Through this mechanism, the internal micro-pores of the foamed concrete are partially closed or modified into hydrophobic channels, significantly reducing the overall water absorption rate and water vapor diffusion rate of the material. At the same time, the hydrophobic barrier layer formed by the self-assembly of wood wax oil molecules on the surface of the nano-channels can inhibit the capillary water migration inside the pores, improving the ability of the concrete to resist freeze-thaw cycle damage and long-term durability. Further, the low-density characteristics of the silica aerogel particles themselves can improve the thermal insulation performance and lightness of the foamed concrete without significantly increasing the material density.

[0029] Further, 0.05 to 0.1 parts by weight of an isocyanate-based reactive prepolymer is added to the foamed concrete.

[0030] By introducing a small amount of isocyanate-based reactive prepolymer (in this invention, isophorone diisocyanate-trimethylolpropane (IPDI-TMP) adduct is mainly used), the interfacial properties of the pore structure of the foamed concrete are further optimized. The isocyanate group (–NCO) has highly reactive chemical properties and can undergo cross-linking reactions with trace amounts of water in the cement-based system or hydroxyl groups (–OH) on the surface of the pore wall during film formation and curing.

[0031] In the foam forming and initial setting stages, the isocyanate-based prepolymer migrates to the surface of the pore film together with the modified wood wax oil, and forms a polyurea bond (–NH–CO–NH–) or a polyurethane bond (–NH–CO–O–) by reacting rapidly with local water, constructing a dense and continuous organic cross-linked network. This cross-linked film can form a stable hydrophobic organic protective layer on the pore wall, effectively improving the mechanical strength and environmental stability of the pore film.

[0032] Due to the excellent flexibility and low-temperature resistance of the formed organic film, it can still maintain good elasticity and continuity within a wide temperature range of -15°C to +50°C, preventing stress concentration, microcrack formation, and cell wall damage caused by sudden temperature changes. Especially in the freeze-thaw cycle environment, the organic film can effectively inhibit the growth and expansion of ice crystals in the pores, reduce the frost heaving stress, and significantly improve the freeze-thaw resistance and long-term durability of the foamed concrete.

[0033] In addition, the low addition amount design of the isocyanate-based prepolymer ensures its efficient reaction in the system without introducing excessive crosslinking points, avoiding over-rigidification of the material, and taking into account both structural stability and overall flexibility. Finally, through the isocyanate crosslinking mechanism, the present invention constructs a highly stable hydrophobic and flexible protective layer on the surface of the micro-pore walls of the foamed concrete, achieving a comprehensive improvement in the high weather resistance, long lifespan, and mechanical properties of the cell structure.

[0034] A preparation method of the above-mentioned foamed concrete modified with wood wax oil specifically includes the following steps: S1: Weigh cement, light sand, polyacrylamide, silica aerogel particles, isocyanate-based reactive prepolymer, and n-pentanol according to the proportion, add them to deionized water, and conduct preliminary stirring. S2: Dissolve the protein foaming agent in deionized water, add it to the pre-prepared mixture of modified wood wax oil and polyoxyethylene polyoxypropylene ether, and continue to stir evenly. S3: Mix the mixture in step S2 with the raw materials in step S1, and conduct sufficient stirring until a concrete slurry with stable foam is formed and evenly mixed. S4: Pour the mixture into a mold, let it stand for 24 hours to complete curing, and obtain the finished product of the foamed concrete.

[0035] Furthermore, in step S2, the stirring temperature is controlled at 50 - 60°C, and the stirring time is 8 - 15 minutes.

[0036] Furthermore, in step S4, the curing process includes first standing at room temperature for 2 - 4 hours, and then curing for 24 - 48 hours under the conditions of a relative humidity of 60 - 75% and a temperature of 25 - 28°C.

[0037] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects: (1) Through grafting esterification reaction, the modified wood wax oil is given appropriate hydrophilicity and surface activity, enabling it to bind well with the cement matrix, thereby improving the water resistance and frost resistance of the foamed concrete without affecting the cement hydration process.

[0038] (2) The modified wood wax oil and polyacrylamide act synergistically to improve the stability and elasticity of the foam film, ensuring the uniformity and durability of the foam during stirring, pouring, and initial setting, thereby enhancing the overall structural integrity of the foamed concrete.

[0039] (3) By adding silica aerogel particles, a nano-capillary network structure with a high specific surface area is constructed, effectively enhancing the lightweight and thermal insulation properties of the foamed concrete. Meanwhile, the isocyanate-based reactive prepolymer forms a hydrophobic protective layer on the cell walls through cross-linking, enhancing the freeze-thaw resistance and long-term mechanical stability of the foamed concrete.

[0040] (4) The polyoxyethylene-polyoxypropylene ether block copolymer induces the formation of micelle structures under temperature response, effectively encapsulating the wood wax oil, and improving the hydration reaction of cement through a temperature-controlled release mechanism, promoting the directional growth of C-S-H gel, and further enhancing the early strength and long-term durability of the foamed concrete. Specific Embodiments

[0041] The present invention will be described in detail below in conjunction with embodiments.

[0042] Example 1 This example discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Lightweight sand: 19 parts; Among them, the cement is P.O 42.5 ordinary Portland cement; The protein foaming agent is the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology Co., Ltd.; The lightweight sand is silica-based lightweight sand with a particle size of 0.3 mm and a mud content of less than 1%; The modified wood wax oil is a graft product after the graft esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65%, and the HLB value is 9.

[0043] The modified wood wax oil is prepared through the following steps: (1) Weigh wood wax oil and nonylphenol polyoxyethylene ether (average number of polyoxyethylene chain segments is 10) and mix them according to a mass ratio of 1:1.2; the wood wax oil is selected with a grade having a saturated fatty acid ester (C17) content of 75% to ensure uniform distribution of the main reaction sites in the reactants; use a magnetic stirrer or mechanical stirring equipment to pre-stir for 12.5 minutes at room temperature (22.5 °C) to fully mix the two raw materials evenly.

[0044] Subsequently, while continuously stirring, titanium tetrafluoride catalyst with a dosage of 1.0 wt% of the total mass of the reaction system was added dropwise. The reaction temperature was controlled at 85 °C, the heating rate was controlled at 3.5 °C / min, and the reaction time was 3 hours.

[0045] (2)After the reaction was completed, it was naturally cooled to room temperature (22.5 °C); if the viscosity of the system increased, a small amount of anhydrous ethanol (mass ratio not exceeding 5%) could be added appropriately to assist in dilution for subsequent operations.

[0046] The cooled reaction mixture was added to pre-cooled anhydrous ethanol (volume ratio 1:5) for precipitation; centrifugation or vacuum filtration was used to remove unreacted nonylphenol polyoxyethylene ether and impurities; the precipitate was washed twice with anhydrous ethanol, 10 minutes each time, for further purification; finally, it was vacuum dried at 45 °C for 7 hours to obtain a pure modified wood wax oil grafted product.

[0047] This example also discloses a preparation method of the above-mentioned foamed concrete modified with wood wax oil, which specifically includes the following steps: S1: After weighing cement and light sand according to the said ratio, they were added to deionized water for preliminary stirring; the stirring time was controlled at 7 minutes; the stirring speed was controlled at 1100 rpm; the stirring temperature was controlled at 27.5 °C.

[0048] S2: The protein foaming agent was dissolved in deionized water at 22.5 °C, the stirring speed was controlled at 350 rpm, and it was stirred for 9 minutes until evenly mixed to ensure that the foaming agent was completely dissolved, generating a uniform foaming agent solution. Subsequently, the modified wood wax oil was added and stirring continued to obtain a mixed solution.

[0049] S3: The mixed solution in step S2 was mixed with the raw materials in step S1, and the stirring time was controlled at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5 °C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: The mixture was poured into a mold, left to stand at room temperature for 3 hours first, and then cured for 24 hours under the conditions of 75% relative humidity and 25 °C temperature to obtain the finished foamed concrete.

[0050] Example 2 This example discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 30 parts; Modified wood wax oil: 7 parts; Protein foaming agent: 0.2 parts; Deionized water: 25 parts; Light sand: 18 parts; Among them, P.O 42.5 ordinary portland cement is used; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The light sand uses siliceous light sand with a particle size of 0.1 mm and a mud content of less than 1%; The modified wood wax oil is a graft product after the grafting esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65% and the HLB value is 8.

[0051] The modified wood wax oil is prepared by the following steps: (1) Weigh wood wax oil and nonylphenol polyoxyethylene ether (average number of polyoxyethylene chain segments is 9) and mix them according to a mass ratio of 1:1.1; The wood wax oil is selected with a grade containing 65% of saturated fatty acid ester (C16) to ensure uniform distribution of main reaction sites in the reactants; Use a magnetic stirrer or mechanical stirring equipment to pre-stir for 10 minutes at room temperature (20 °C) to fully mix the two raw materials evenly.

[0052] Subsequently, while continuously stirring, add titanium tetrafluoride catalyst with a dosage of 0.5 wt% of the total mass of the reaction system dropwise, control the reaction temperature at 80 °C, the heating rate at 2 °C / min, and the reaction time at 2 hours.

[0053] (2) After the reaction is completed, naturally cool to room temperature (20 °C); If the viscosity of the system increases, a small amount of anhydrous ethanol (mass ratio not exceeding 5%) can be added appropriately for auxiliary dilution for subsequent operations.

[0054] Add the cooled reaction mixture to pre-cooled anhydrous ethanol (volume ratio 1:5) for precipitation; Use centrifugal separation or vacuum filtration to remove unreacted nonylphenol polyoxyethylene ether and impurities; Wash the precipitate with anhydrous ethanol twice, 10 minutes each time, for further purification; Finally, vacuum dry at 40 °C for 6 hours to obtain a pure modified wood wax oil graft product.

[0055] This embodiment also discloses a preparation method of the above-mentioned foamed concrete modified with wood wax oil, which specifically includes the following steps: S1: After weighing cement and light sand according to the above ratio, add deionized water and conduct preliminary stirring; Control the stirring time to 6 minutes; Control the stirring speed to 1000 rpm; Control the stirring temperature to 25 °C.

[0056] S2: Dissolve the protein foaming agent in deionized water at 20 °C, control the stirring speed at 300 rpm, stir for 9 minutes until evenly stirred to ensure complete dissolution of the foaming agent, generate a uniform foaming agent solution, and then add the modified wood wax oil and continue stirring to obtain a mixed solution.

[0057] S3: Mix the mixture in step S2 with the raw materials in step S1, and control the stirring time to be 8 minutes, the stirring speed to be 1200 rpm, and the stirring temperature to be 20°C for thorough stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of 75% relative humidity and 25°C temperature to obtain the finished foamed concrete.

[0058] Example 3 This example discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 40 parts; Modified wood wax oil: 9 parts; Protein foaming agent: 0.4 part; Deionized water: 35 parts; Lightweight sand: 20 parts; Among them, the cement uses P.O 42.5 ordinary Portland cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The lightweight sand uses silica-based lightweight sand with a particle size of 0.5 mm and a mud content of less than 1%; The modified wood wax oil is a grafted product after the grafting esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the grafted product is not less than 65% and the HLB value is 11.

[0059] The modified wood wax oil is prepared through the following steps: (1) Weigh and mix wood wax oil and nonylphenol polyoxyethylene ether (average number of polyoxyethylene chain segments is 11) according to a mass ratio of 1:1.3; the wood wax oil selects a grade with a saturated fatty acid ester (C18) content of 85% to ensure uniform distribution of the main reaction sites in the reactants; use a magnetic stirrer or mechanical stirring equipment to pre-stir for 15 minutes at room temperature (25°C) to fully mix the two raw materials evenly.

[0060] Subsequently, continuously stir and dropwise add titanium tetrafluoride catalyst with a dosage of 1.5 wt% of the total mass of the reaction system, control the reaction temperature at 90°C, the heating rate at 5°C / min, and the reaction time at 4 hours.

[0061] (2) After the reaction is completed, naturally cool to room temperature (25°C); if the system viscosity increases, a small amount of anhydrous ethanol (mass ratio not exceeding 5%) can be appropriately added for auxiliary dilution for subsequent operations.

[0062] The cooled reaction mixture was added to pre-cooled absolute ethanol (volume ratio 1:5) for precipitation; centrifugal separation or vacuum filtration was used to remove unreacted nonylphenol polyoxyethylene ether and impurities; the precipitate was washed 3 times with absolute ethanol, each time for 10 minutes for further purification; finally, it was dried in vacuo at 50 °C for 8 hours to obtain a pure modified wood-wax oil grafted product.

[0063] This example also discloses a preparation method of the above-mentioned foamed concrete modified with wood-wax oil, which specifically includes the following steps: S1: After weighing cement and light sand in the stated proportions, they were added to deionized water and subjected to preliminary stirring; the stirring time was controlled at 8 minutes; the stirring speed was controlled at 1200 rpm; the stirring temperature was controlled at 30 °C.

[0064] S2: The protein foaming agent was dissolved in deionized water at 55 °C, the stirring speed was controlled at 400 rpm, and stirring was carried out for 9 minutes until evenly mixed to ensure complete dissolution of the foaming agent, generating a uniform foaming agent solution. Subsequently, modified wood-wax oil was added and stirring was continued to obtain a mixed solution.

[0065] S3: The mixed solution from step S2 was mixed with the raw materials in step S1, and stirring was carried out for 10 minutes, the stirring speed was 1500 rpm, and the stirring temperature was 25 °C for thorough stirring until evenly mixed to form a concrete slurry with stable foam; S4: The mixture was poured into a mold, left to stand at room temperature for 3 hours first, and then cured for 24 hours under the conditions of 75% relative humidity and 25 °C to obtain the finished foamed concrete.

[0066] Example 4 This example discloses a foamed concrete modified with wood-wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood-wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Light sand: 19 parts; Polyacrylamide: 1.5 parts.

[0067] Among them, the cement used was P.O 42.5 ordinary Portland cement; The protein foaming agent used was the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The light sand used was siliceous light sand with a particle size of 0.3 mm and a mud content of less than 1%; The modified wood-wax oil was a grafted product after the grafting esterification reaction of nonylphenol polyoxyethylene ether and wood-wax oil, and the esterification rate of the grafted product was not less than 65% and the HLB value was 9.

[0068] The preparation method of the modified wood wax oil is the same as that of Example 1.

[0069] This example also discloses a preparation method of the above foamed concrete modified with wood wax oil, which specifically includes the following steps: S1: After weighing cement, light sand, and polyacrylamide according to the said ratio, add them into deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5°C.

[0070] S2: Dissolve the protein foaming agent in deionized water at 50°C, control the stirring speed at 350 rpm, and stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generating a uniform foaming agent solution. Subsequently, add the modified wood wax oil and continue stirring to obtain a mixed solution.

[0071] S3: Mix the mixed solution in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5°C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of 75% relative humidity and 25°C temperature to obtain the finished foamed concrete.

[0072] Example 5 This example discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Light sand: 19 parts; Polyacrylamide: 1.5 parts; n-Amyl alcohol: 0.3 part.

[0073] Among them, the cement uses P.O 42.5 ordinary Portland cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The light sand uses silica light sand with a particle size of 0.3 mm and a mud content of less than 1%; The modified wood wax oil is a graft product after the graft esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65% and the HLB value is 9.

[0074] The preparation method of the modified wood wax oil is the same as that of Example 1.

[0075] This embodiment also discloses a preparation method of the above-mentioned foamed concrete modified with wood wax oil, which specifically includes the following steps: S1: After weighing cement, light sand, polyacrylamide, and n-pentanol according to the said proportions, add them to deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5 °C.

[0076] S2: Dissolve the protein foaming agent in deionized water at 50 °C, control the stirring speed at 350 rpm, and stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generating a uniform foaming agent solution. Subsequently, add the modified wood wax oil and continue stirring to obtain a mixture.

[0077] S3: Mix the mixture in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5 °C for sufficient stirring until evenly mixed to form a concrete paste with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of 75% relative humidity and 25 °C temperature to obtain the finished foamed concrete.

[0078] Example 6 This embodiment discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Light sand: 19 parts; Polyacrylamide: 1.5 parts; n-Pentanol: 0.3 part; Polyoxyethylene polyoxypropylene ether: 2 parts.

[0079] Among them, the cement uses P.O 42.5 ordinary Portland cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The light sand uses silica light sand with a particle size of 0.3 mm and a mud content of less than 1%; The polyoxyethylene polyoxypropylene ether uses Pluronic F127; The modified wood wax oil is a graft product after the graft esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65%, and the HLB value is 9.

[0080] The preparation method of the modified wood wax oil is the same as that in Example 1.

[0081] This embodiment also discloses a preparation method of the above-mentioned foamed concrete modified with wood wax oil, which specifically includes the following steps: S1: After weighing cement, light sand, polyacrylamide, and n-pentanol according to the said proportions, add them to deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5 °C.

[0082] S2: Dissolve the protein foaming agent in deionized water at 55 °C, control the stirring speed at 350 rpm, and stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generating a uniform foaming agent solution; Premix the modified wood wax oil and polyoxyethylene polyoxypropylene ether by stirring at 30 °C to form an emulsified premix, and then mix it with the foaming agent solution and continue stirring to obtain a mixed solution.

[0083] S3: Mix the mixed solution in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5 °C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of a relative humidity of 75% and a temperature of 25 °C to obtain the finished foamed concrete.

[0084] Example 7 This embodiment discloses a foamed concrete modified with wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Light sand: 19 parts; Polyacrylamide: 1.5 parts; n-Pentanol: 0.3 part; Polyoxyethylene polyoxypropylene ether: 2 parts; Silica aerogel particles: 1 part.

[0085] Among them, the cement uses P.O 42.5 ordinary Portland cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology Co., Ltd.; The light sand uses silica-based light sand with a particle size of 0.3 mm and a mud content of less than 1%; The D50 particle size of the silica aerogel particles is 50 nm; The polyoxyethylene polyoxypropylene ether uses Pluronic F127; The modified wood wax oil is a graft product after the graft esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65%, and the HLB value is 9.

[0086] The preparation method of the modified wood wax oil is the same as that of Example 1.

[0087] This example also discloses a preparation method of the above-mentioned foamed concrete modified based on wood wax oil, which specifically includes the following steps: S1: After weighing cement, light sand, silica aerogel particles, polyacrylamide, and n-pentanol in the said proportions, add them to deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5 °C.

[0088] S2: Dissolve the protein foaming agent in deionized water at 55 °C, control the stirring speed at 350 rpm, and stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generating a uniform foaming agent solution; Stir and premix the modified wood wax oil and polyoxyethylene polyoxypropylene ether at 30 °C to form an emulsified premix, and then mix it with the foaming agent solution and continue stirring to obtain a mixed solution.

[0089] S3: Mix the mixed solution in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5 °C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, first let it stand at room temperature for 4 hours, and then cure it for 24 hours under the conditions of 75% relative humidity and 25 °C temperature to obtain the finished foamed concrete.

[0090] Example 8 This example discloses a foamed concrete modified based on wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Modified wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Light sand: 19 parts; Polyacrylamide: 1.5 parts; n-Pentanol: 0.3 part; Polyoxyethylene polyoxypropylene ether: 2 parts; Silica aerogel particles: 1 part; Isocyanate-based reactive prepolymer: 0.08 part.

[0091] Among them, P.O 42.5 ordinary Portland cement is used for the cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The lightweight sand uses silica lightweight sand with a particle size of 0.3 mm, and the mud content is less than 1%; The D50 particle size of the silica aerogel particles is 50 nm; The polyoxyethylene polyoxypropylene ether uses Pluronic F127; The isocyanate-type reactive prepolymer is an IPDI-TMP adduct.

[0092] The modified wood wax oil is a graft product after the graft esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the graft product is not less than 65%, and the HLB value is 9.

[0093] The preparation method of the modified wood wax oil is the same as that of Example 1.

[0094] This example also discloses a preparation method of the above-mentioned foamed concrete modified based on wood wax oil, which specifically includes the following steps: S1: After weighing cement, lightweight sand, silica aerogel particles, isocyanate-type reactive prepolymer, polyacrylamide, and n-pentanol according to the above proportions, add them to deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5 °C.

[0095] S2: Dissolve the protein foaming agent in deionized water at 60 °C, control the stirring speed at 350 rpm, and stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generating a uniform foaming agent solution; Pre-mix the modified wood wax oil and polyoxyethylene polyoxypropylene ether by stirring at 30 °C to form an emulsified premix, and then mix it with the foaming agent solution and continue stirring to obtain a mixed solution.

[0096] S3: Mix the mixed solution in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5 °C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of a relative humidity of 75% and a temperature of 25 °C to obtain the finished foamed concrete.

[0097] Comparative Example 1 This example discloses a foamed concrete modified based on wood wax oil, and its raw materials mainly include the following components in parts by weight: Cement: 35 parts; Wood wax oil: 8 parts; Protein foaming agent: 0.3 part; Deionized water: 30 parts; Lightweight sand: 19 parts; Among them, the cement uses P.O 42.5 ordinary Portland cement; The protein foaming agent uses the 1261# type foaming agent of Dongguan Shenhai Energy Saving Building Materials Technology; The lightweight sand uses silica-based lightweight sand with a particle size of 0.3 mm and a mud content of less than 1%; Comparative Example 1 also discloses a preparation method of the above foamed concrete, which specifically includes the following steps: S1: After weighing the cement and lightweight sand according to the above ratio, add them to deionized water and conduct preliminary stirring; the stirring time is controlled at 7 minutes; the stirring speed is controlled at 1100 rpm; the stirring temperature is controlled at 27.5°C.

[0098] S2: Dissolve the protein foaming agent in deionized water at 22.5°C, control the stirring speed at 350 rpm, stir for 9 minutes until evenly stirred to ensure that the foaming agent is completely dissolved, generate a uniform foaming agent solution, and then add wood wax oil and continue to stir to obtain a mixture.

[0099] S3: Mix the mixture in step S2 with the raw materials in step S1, and control the stirring time at 9 minutes, the stirring speed at 1350 rpm, and the stirring temperature at 22.5°C for sufficient stirring until evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, let it stand at room temperature for 3 hours first, and then cure it for 24 hours under the conditions of relative humidity of 75% and temperature of 25°C to obtain the finished foamed concrete.

[0100] Testing method 1. Early strength test of concrete slurry Testing method: The specific testing steps are as follows: Step 1: Prepare specimens with standard dimensions (100 mm × 100 mm × 100 mm cube).

[0101] Step 2: After the concrete specimens are formed, cure them at room temperature for 24 hours, and then transfer them to standard curing conditions (humidity maintained at 95%, temperature 25°C) for continued curing.

[0102] Step 3: Use a press (such as a 2000 kN pressure testing machine) to conduct a compressive strength test, and record the compressive strength at 24 hours and 48 hours.

[0103] The test results are shown in Table 1.

[0104] Table 1 2. Concrete durability test Test method: Test according to the GB / T 50082 standard by using a standard water permeameter.

[0105] Step 1: Make standard specimens (100mm×100mm×100mm cubes) Step 2: Place the concrete specimens in a pressurized water penetration device, apply a standard water pressure (e.g., 0.2 MPa), and soak for 48 hours continuously.

[0106] Step 3: Evaluate the water resistance of the concrete according to the penetration depth or mass change.

[0107] The test results are shown in Table 2.

[0108] Table 2 3. Foam stability test: Evaluate by using a foam stability tester.

[0109] Step 1: Pour the foamed concrete slurry into a standard foam container and record the initial foam height.

[0110] Step 2: As time goes by, measure the foam height every 5 minutes until it breaks, and record the foam duration.

[0111] The test results are shown in Table 3.

[0112] Table 3 4. Frost resistance and thawing cycle resistance Test method: Test according to the ASTM C666 standard.

[0113] Step 1: Prepare the concrete samples into standard sizes (100mm×100mm×100mm cubes) and freeze them after initial curing for 24 hours.

[0114] Step 2: Alternately place the specimens in an environment of -20°C for 4 hours of freezing and then in an environment of 20°C for 4 hours of thawing. Conduct 25 freeze-thaw cycles for each period.

[0115] Step 3: After the freeze-thaw cycle is completed, measure the compressive strength loss and mass change of the concrete as the evaluation indicators of frost resistance and thawing cycle resistance.

[0116] The test results are shown in Table 4.

[0117] Table 4 The above are only the preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions falling within the concept of the present invention belong to the protection scope of the present invention. It should be noted that for those of ordinary skill in the art, several improvements and refinements made without departing from the principle of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A foamed concrete modified with wood wax oil, characterized in that, It is prepared from the following components in parts by weight: Cement: 30 - 40 parts; Modified wood wax oil: 7 - 9 parts; Protein foaming agent: 0.2 - 0.4 part; Deionized water: 25 - 35 parts; Lightweight sand: 18 - 20 parts; The modified wood wax oil is a grafted product after the grafting esterification reaction of nonylphenol polyoxyethylene ether and wood wax oil, and the esterification rate of the grafted product is not less than 65%, and the HLB value is 8 - 11.

2. A foamed concrete modified with wood wax oil according to claim 1, characterized in that: The modified wood wax oil is prepared through the following steps: (1) Mix wood wax oil and nonylphenol polyoxyethylene ether according to a mass ratio of 1:1.1 - 1.3, add titanium tetrafluoride catalyst with a dosage of 0.5 - 1.5 wt% of the total mass of the reaction system, and carry out heating reaction; the reaction temperature is controlled at 80 - 90 °C, and the reaction time is 2 - 4 hours; Among them, the average EO unit number of nonylphenol polyoxyethylene ether is 9 - 11; the content ratio of C16 - C18 saturated fatty acid esters in the used wood wax oil is 65 - 85%; (2) Remove unreacted components by solvent to obtain the modified wood wax oil grafted product.

3. A foamed concrete modified with wood wax oil according to claim 1, characterized in that: 1 - 2 parts by weight of polyacrylamide is also added to the foamed concrete.

4. A foamed concrete modified with wood wax oil according to claim 3, characterized in that: 0.1 - 0.5 part by weight of n - pentanol is also added to the foamed concrete.

5. A foamed concrete modified with wood wax oil according to claim 4, characterized in that: 1 - 3 parts by weight of polyoxyethylene polyoxypropylene ether is also added to the foamed concrete, and the modified wood wax oil and polyoxyethylene polyoxypropylene ether are pre - mixed at 25 - 35 °C to form an emulsified premix, and then mixed with other components together to prepare the foamed concrete.

6. A foamed concrete modified with wood wax oil according to claim 5, characterized in that: 0.5 - 1.5 parts by weight of silica aerogel particles is also added to the foamed concrete, and the D50 particle size of the silica aerogel particles is 30 - 50 nm.

7. A foamed concrete modified with wood wax oil according to claim 6, characterized in that: 0.05 - 0.1 part by weight of isocyanate - type reactive prepolymer is also added to the foamed concrete.

8. A preparation method of foamed concrete modified with wood wax oil according to claim 7, characterized in that, Specifically, it includes the following steps: S1: Weigh cement, lightweight sand, polyacrylamide, silica aerogel particles, isocyanate - type reactive prepolymer, and n - pentanol according to the proportion, add them into deionized water, and carry out preliminary stirring; S2: Dissolve the protein foaming agent in deionized water, add it to the pre - prepared mixture of modified wood wax oil and polyoxyethylene polyoxypropylene ether, and continue to stir evenly; S3: Mix the mixture in step S2 with the raw materials in step S1, and carry out sufficient stirring until it is evenly mixed to form a concrete slurry with stable foam; S4: Pour the mixture into a mold, stand for 24 hours to complete curing, and obtain the finished product of foamed concrete.

9. The preparation method of a foamed concrete modified with wood wax oil according to claim 8, characterized in that: In step S2, the stirring temperature is controlled at 50 - 60 °C, and the stirring time is 8 - 15 minutes.

10. The preparation method of a kind of foamed concrete modified by wood wax oil according to claim 8, characterized in that, In step S4, the curing process includes standing at room temperature for 2 - 4 hours first, and then curing for 24 - 48 hours under the conditions of relative humidity of 60 - 75% and temperature of 25 - 28 °C.

Citation Information

Patent Citations

  • Novel antique building material and preparation method thereof

    CN105601219A

  • Water-based wax oil composition and preparation method thereof

    CN107955530A

  • Composite steel fiber reclaimed rubber concrete

    CN110117177A

  • Lightweight energy-saving foam concrete and preparation method thereof

    CN114560667A

  • Concrete targeting agent and preparation method thereof

    CN117567062A